2019
DOI: 10.3390/app9010127
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Heat Input Controllability of Two Different Modulations for Double-Pulse MIG Welding

Abstract: Aluminum alloy welding frequently experiences difficulties such as heat input control, poor weld formation, and susceptibility to pore generation. We compared the use of two different modulations for double-pulse metal inert gas (MIG) welding to reduce the heat input required to generate oscillations in the weld pool. The stabilities of rectangular wave-modulated and trapezoidal wave-modulated double-pulse MIG welding (DP-MIG and TP-MIG) were analyzed by examining their welding processes and weld profiles. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Under the impact of droplets, the stirring effect of the molten pool was enhanced. Therefore, the more uniform distribution of grains in the ODPP condition could be obtained, even though the average current and heat input were similar in ODPP and MDPP conditions [27].…”
Section: Microstructure Analysis Of Weldmentioning
confidence: 97%
“…Under the impact of droplets, the stirring effect of the molten pool was enhanced. Therefore, the more uniform distribution of grains in the ODPP condition could be obtained, even though the average current and heat input were similar in ODPP and MDPP conditions [27].…”
Section: Microstructure Analysis Of Weldmentioning
confidence: 97%
“…T HE concept of controllability denotes the ability to move a robotic arm around in its entire configuration space using only certain admissible manipulations. The exact definition varies slightly within the framework or the kind of applied robotic arms [1], [2], [3]. Controllability and observability are dual aspects of the same problem.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the current research on DP-GMAW is mainly focuses on the following two aspects: reducing the heat input and increasing the stirring effect of the molten pool. First, the heat input during the welding process can be reduced by using different current waveforms, such as median pulsed current waveform [15], trapezoidal wave-modulated current waveform [16], and gaussian pulsed current waveform [17]. Wu et al [18] introduced a dual-wire DP-GMAW with a median current waveform based on the conventional rectangular pulse and found that changed the median current, the average welding current also changed.…”
Section: Introductionmentioning
confidence: 99%